Public sector ICT strategic planning: framework of monitoring and evaluating process - Suhaiza Sudirman; Zawiyah Mohammad Yusof (Penerbit Universiti Kebangsaan Malaysia, 2017)
A successful implementation of the ICT strategic plan (ISP) lies in the monitoring and evaluation (M&E) practice. However, M&E is often neglected due to the usage of impractical methods. Furthermore, the current ISP methodology does not account for M&E process. M&E should be appropriate to the organization’s environment and accordingly fits the characteristics of the type of planning. This study aims to identify strategic planning M&E processes and activities to produce the best practice of M&E process for ISP implementation vis a vis serve as a guide to public organizations. The Malaysia public sector was chosen as a case study with interview and documents analysis as data collection techniques.The results revealed that the M&E process involves four phases and 10 steps which were then used as the basis for the development of the proposed framework that are named as MEISP framework. The framework could serve as a guide for the public agencies for practicing M&E for the ISP implementation.